Środki katechizacji w ujęciu prawa kanonicznego - Adamczyk, Jerzy (Poznańskie Studia Teologiczne, 2020)
This arcticle refers to the issue of means of catechesis in the canonical aspect. Firstly, there have been shown the rules which relate to necessity of using aids of catechetical activity. Then, it has been concentrated about issues of instruments dedicated to the orientation and general planning of catechetical activity in particular Church. Next it has been explained matter of catechisms and other writings pertaining to catechetical instruction. Finally, it has been focused on adio-visual aids and instruments of social communication in catechetical formation.